Application of Contemplative Education to Enhance Nursing Students’ Skills in Mental Health and Psychiatric Nursing - Ruangkit, Phannapa; Chawajaroenpan, Wanida; Sanguanprasit, Boosaba (Journal of The Royal Thai Army Nurses, 2023)
This classroom action research aimed to evaluate the results of applying contemplative education principles in designing mental health and psychiatric nursing practicum learning activities in getting students ready in all aspects- mental, emotional, and required knowledge, skills, and attitudes. As such, they would be able to plan and provide nursing care to the patients in accordance with Mental Health and Psychiatric Nursing process with caring behaviors. Samples were 24 third-year nursing students enrolling in the Mental Health and Psychiatric Nursing practicum and under supervision of the principal investigator. Research instruments included learning activities applying contemplative education principles to get students ready for their practices in the Mental Health and Psychiatric ward. Qualitative methods including observing students’ verbal and non-verbal behaviors, queries, nursing care plan, and students’ journals were used for evaluation. Data were analyzed by using content analysis. Results showed that the preparation activities applying contemplative education principles could improve students’ concentration, communication and inter-personal interactions, self-awareness, caring behaviors, acceptance of individual differences; reduce their nervousness and anxiety. Such changes made them enjoy their clinical practice and able to build good relationship and trust among the patients, develop nursing care plan and provide effective care to the patients in accordance with Mental Health and Psychiatric Nursing process with caring behaviors.